The influence of species identity and geographic locations on gut microbiota of small rodents - Wang, Zhenyu; Zhang, Chao; Li, Guoliang; Yi, Xianfeng (Frontiers in Microbiology, 2022)
Although the correlation between gut microbiota, species identity and geographic locations has long attracted the interest of scientists, to what extent species identity and geographic locations influence the gut microbiota assemblages in granivorous rodents needs further investigation. In this study, we performed a survey of gut microbial communities of four rodent species (Apodemus agrarius, A. peninsulae, Tamias sibiricus and Clethrionomys rufocanus) distributed in two areas with great distance (> 600 km apart), to assess if species identity dominates over geographic locations in shaping gut microbial profiles using 16S rRNA gene sequencing. We found that gut microbiota composition varied significantly across host species and was closely correlated with host genetics. We identified strong species identity effects on gut microbial composition, with a comparatively weaker signal of geographic provenance on the intestinal microbiota. Specifically, microbiota of one species was on average more similar to that of conspecifics living in separate sites than to members of a closely related species living in the same location. Our study suggests that both host genetics and geographical variations influence gut microbial diversity of four rodent species, which merits further investigation to reveal the patterns of phylogenetic correlation of gut microbial community assembly in mammals across multiple habitats.